The purine transferase from Trypanosoma cruzi as a potential target for bisphosphonate-based chemotherapeutic compounds - Fernández, Daniel (2004)
We identified and tested bisphosphonates as inhibitors of a protozoan molecular target. Computational modeling studies demonstrated that these compounds are mimics of the natural substrate of the enzyme. The most potent bisphosphonates in vitro are pamidronate and risedronate, which inhibit the purine transferase from Trypanosoma cruzi in the micromolar range.